CODE MIXING AND SWITCHING IN THE OPENING SPEECH OF SUSILO BAMBANG YUDHOYONO IN THE NTERNATIONAL CONFERENCE FOR ANTI-CORRUPTION AGENCIES - PRASETYO, DENNDY IRAWAN ARDI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Code Mixing, Code switching, Susilo Bambang Yudhoyono Nowadays, we often meet the phenomenon of using two or more languages in communication. In this case, there are some ways to distribute code mixing and switching. This study analyzes code mixing and switching focusing on the speech of Susilo Bambang Yudhoyono. SBY is the sixth president of Republik Indonesia who deliver the speech entitled “Sambutan Presiden Republik Indonesia Menerima Pimpinan Delegasi International Conference Principles for  Anti-Corruption Agencies”. In his speech, SBY frequently used certain words fromforeign language, especially English. This research attempts to identify the typesof code mixing and switching used by SBY and also the influencing factors ofSBY to use code mixing and switching in his speech. This research uses theoryproposed by Holmes (1992). For the research methods, the writer used qualitative approach and the object of this research is SBY’s speech entitled “Sambutan Presiden Republik Indonesia Menerima Pimpinan Delegasi International Conference Priciples for Anti-Corruption Agencies”. The writer collected 48 data which contain codemixing and switching. In collecting the data, the writer did several steps namely,downloading the script, choosing the utterance which contain of code mixing andswitching. This research found that there are some of types of code mixing and switching used by SBY in his speech. They are situational and metaphorical code mixing and situational code switching. This research also found the factors that influence SBY to use code mixing and switching. They are function, topic,participant, and setting.In conclusion, the writer found significant relevance between theinfluencing factors and the types of code mixing and switching. Hopefully thisresearch can be used as an additional reference for the next researchers whoconcern on both code mixing and switching.